Meckel’s Diverticulum Diagnosed by Balloon-Assisted Enteroscopy: A Multicenter Report from the Taiwan Association for the Study of Small Intestinal Diseases (TASSID) - Jen-Wei Chou; Chen-Shuan Chung; Tien-Yu Huang; Chia-Hung Tu; Chen-Wang Chang; Chung-Hsin Chang; Yen-Po Wang; Wen-Hung Hsu; Hsu-Heng Yen; Chia-Jung Kuo; Chiao-Hsiung Chuang; Ching-Pin Lin; et al. (Gastroenterology Research and Practice)
Background and Aims. Patients with Meckel’s diverticulum (MD) are difficult to preoperatively diagnose because of its endoscopic inaccessibility. Balloon-assisted enteroscopy (BAE) allows endoscopic access to the entire small intestine. The aim of the current study was to investigate patients with MD diagnosed by BAE in Taiwan. Methods. We conducted a retrospective, multicenter study of patients with MD who were diagnosed by BAE in Taiwan. The clinical characteristics, endoscopic features, histopathological findings, treatment methods, and outcomes were analyzed. Results. A total of 55 patients with MD were enrolled (46 males and 9 females). The mean age at diagnosis was 34.1 years. Overt gastrointestinal bleeding (87.3%) was the primary indication for BAE, followed by abdominal pain (9.1%), suspected small bowel tumor (1.8%), and Crohn’s disease follow-up (1.8%). The mean distance between the ileocecal valve and MD was 71.6 cm (regarding diagnostic yields: BAE—100%, capsule endoscopy—40%, Meckel’s scan—35.7%, computed tomography—14.6%, small bowel series—12.5%, and angiography—11.1%; regarding endoscopic features of MD: a large ostium—89.1%, a small ostium—7.3%, and a polypoid mass—3.6%). Surgical treatment was performed in 76.4% patients, and conservative treatment was performed in 23.6% patients. The mean length of MD in 42 patients who underwent surgical resection was 5.2 cm (in 43 patients of MD with available histopathology: heterotopic gastric tissue, 42.4%, heterotopic gastric and pancreatic tissues, 7%; heterotopic pancreatic tissue, 4.7%; heterotopic colonic tissue, 2.3%; and a neuroendocrine tumor, 2.3%). Conclusions. The current study showed BAE is a very useful modality for detecting MD compared with other conventional modalities.